Advancing Professional Development in Health Literacy: The Health Literacy Specialist Certificate Program and the Health Literacy Solutions Center. Issue 6 (2nd November 2021) - Gonzalez, Diana Peña; Villaire, Michael
ABSTRACT: Healthy People 2030 has expressed the need for increased organizational health literacy. In order to support this growing effort, the Institute for Healthcare Advancement has developed 2 resources to help support health education professional development: The Health Literacy Specialist Certificate Program as a rigorously designed professional development program; and The Health Literacy Solutions Center, an aid for professionals to network with one another and enhance their health literacy skills and knowledge. In 2016, a Job Analysis Task Force analyzed the requisite knowledge and skills one must possess to be considered a Health Literacy Specialist. From this convening, and with the support of several subject matter experts, the 7 micro-credentials comprising the Health Literacy Specialist Certificate are available for those interested in enhancing their knowledge and skills in health literacy. The Health Literacy Solutions Center is a community portal for professionals interested in enhancing their professional networks and advancing their skills in health literacy. The community contains more than 10, 000 members and is a centralized to receive continuing education on the latest health literacy best practices and issues of interest to this community. This article will describe these resources in detail and its alignment with NCHEC Responsibilities and Competencies.